The Effect Of Service Quality On Customer Satisfaction At PT Pdam Tirta Manna, South Bengkulu District - Weko Hendriansyah; Yudi Irawan Abi; M Rahman Febliansa (Universitas Dehasen Bengkulu, 2026)
This type of research uses quantitative research. The analysis method in this study uses Validity Test, Reliability Test, Multiple Linear Regression Analysis, Determination Coefficient and hypothesis testing using t-test. The number of samples studied was 35 customers who came with complaints and new installations during the last 1 month at PDAM Tirta Manna, South Bengkulu Regency. The results of the multiple linear regression analysis are the equation: Y = 6.450 + 0.052 X1 + 0.084 X2 + 0.227 X3 + 0.288 X4 + 0.234 X5 + e, this describes a positive regression direction, meaning that the variables Physical evidence (X1), Reliability (X2), Assurance (X3), responsiveness (X4), and empathy (X5) have a positive influence on consumer satisfaction (Y) at PDAM Tirta Manna, South Bengkulu Regency. The value of the coefficient of determination from the calculation results using SPSS can be seen from the coefficient of determination value of R square of 0.991. This means that the value of Physical evidence (X1), reliability value (X2), assurance (X3), responsiveness (X4) and empathy (X5) has an effect on consumer satisfaction (Y) of 99.1% while the remaining 0.9% is influenced by other variables not examined in the study.